PENGALAMAN, KOMPLEKSITAS TUGAS DAN SELF EFFICACY SEBAGAI DETERMINAN SKEPTISISME PROFESIONAL UNTUK MEMBENTUK AUDIT JUDGMENT - Tangke, Paulus; Ng, Suwandi; Tungadi2, Erica (School of Accountancy, University of Agung Podomoro, 2020)
This study aims to analyze the influence of Experience, Task Complexity, and Self Efficacy on auditjudgment through Professional Skepticism as an intervening variable. The population in this study is aPublic Accounting Firm in Indonesia, which is listed on the Indonesian Public Accounting FirmDirectory 2018. The sample in this study was 14 Public Accounting Firm in Sulawesi and usingpurposive sampling method. Sources of data in this study are primary data collected throughquestionnaires. This study use multiple linear regression analysis and path analysis.The resultsshowed that experience has a negative and not significant on professional skepticism, task complexityhas a negative and significant on professional skepticism, self efficacy has a positive and significant onprofessional skepticism. Experience, self efficacy, and professional skepticism has a positive andsignificant on audit judgment. Task complexity has a negative and significant on audit judgment.Professional skepticism can not mediate the relationship between experience on audit judgment.Professional skepticism may mediate the task complexity and self efficacy on audit judgment.